Características da ilha de poluição do ar urbana na região metropolitana de São Paulo: uma abordagem combinando dados de satélite e de superfície - Camacho, Fabian Leonardo Moreno (2022)
The urban population growth leads to urban development and expansion, causing an increase in the concentrations of atmospheric pollutants (for example, particulate matter and nitrogen oxides). This gives rise to a phenomenon coined “Urban Air Pollution Island (UPI)”, in which air pollution levels are higher in urban areas than in the periphery. This dissertation aimed to identify the UPI using combined data from satellite (Aerosol Optical Depth, AOD) and air quality monitoring stations (fine particulate matter, PM2.5 and ozone, O3), in the megacity of São Paulo and its metropolitan region (MASP) in the year 2019. The diurnal and seasonal cycles and the spatial variability of these pollutants were analyzed. The occurrence of UPI was investigated through the AOD gradient (ΔAOD) between the urban and peripheral areas, and the PM2.5 (ΔPM2.5) and O3 (ΔO3) gradients between urban stations and the reference station (IBIRA, located at Ibirapuera Park). The diurnal cycles showed highly variable PM2.5 concentrations at all monitoring stations (except for IBIRA), and maximum (minimum) O3 concentrations between 14:00 and 15:00h (7:00h and 8:00h). From the seasonal standpoint, the highest mean PM2.5 concentration (21.5 μg m-3) and the lowest O3 (29 μg m-3) and AOD (0.10) values were observed in May–July. The August–October quarter had the highest mean O3 concentrations (29 μg m-3) and between November–January, the highest AOD (0.16) and lowest PM2.5 (13.9 μg m-3) values. In comparison with the stations in the urban core, the peripheral stations had the highest mean PM2.5 (16–20 μg m-3) and the lowest mean O3 concentrations (34-42 μg m-3). The mean annual AOD value decays exponentially from the urban core (0.137) towards the periphery (R = -0.99). Regarding the UPI, the mean ΔPM2.5 ranged between -1.8 and 14 μg m-3 for the monthly, hourly and weekday cycles, with positive ΔPM2.5 during most of the day (between 14 and 9 h), and ΔPM2.5 lower in the urban core than in the periphery. From the ΔO3 standpoint, negative values prevailed (between -0.02 and -27.4 μg m-3), i.e., higher O3 concentrations at the reference site than at the periphery. The ΔAOD showed higher values in the core of the MASP, with a mean annual value of 0.02. From a seasonal standpoint, ΔPM2.5, ΔO3 and ΔAOD vary throughout the year, being influenced by atmospheric emissions and meteorological variables (air temperature, solar radiation, wind speed and relative humidity), which govern the intensity of the UPI. In closing, the UPI was observed for the AOD and O3 data, but not for PM2.5. The absence of the UPI for PM2.5 is attributed to the location of industries and high vehicular traffic on highways and ring roads on the city's outskirts. On the other hand, the reference site is relatively far from anthropogenic emission sources, with lower concentrations of O3 depleting species, yielding higher O3 concentrations than at the surrounding sites.